PENINGKATAN KETERAMPILAN MENULIS PARAGRAF MELALUI MEDIA PUZZLE PADA SISWA KELAS III SD N REJOWINANGUN 1 YOGYAKARTA - Intan nur Fitriyani; Siti Anafiah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
This research was aimed at describing the improvement of skill in writing paragraph using puzzle for students of grade III at SD Negeri Rejowinangun 1 Yogyakarta. The type of this research was  Classroom Action  Research  (CAR)  which  was  conducted  in  two  cycles.  The  result  of  this research showed that by using puzzle as the media could improve the skill in writing paragraph for students in class IIIA at SD Negeri Rejowinangun 1 Yogyakarta. The students’ mean score obtained in the pre-test was 65,08 and increased into 78,4 in the post-test of Cycle I and then become 83,16 in the post-test of Cycle II. Based on the result of the research above, it could be concluded that the use of puzzle as the media could improve third grade students’ skill in writing paragraphs at SD Negeri Rejowinangun 1 Yogyakarta.